O viés estruturalista da abordagem discursiva de Norman Fairclough - CASTRO, Luciana Andrade Cavalcante de (2011)
The present research intends to explain the constitution of the Structuralist aspects of the discursive approach of Norman Fairclough, one of the most representative authors of Critical Discourse Analysis (CDA). As a methodological and theoretical approach, whose purpose consists in the study of the language in contemporary societies, Critical Discourse Analysis is derived from Critical Linguistics of 1970, consolidating itself in the decade of 1990s. As it borrowed the Social Theory of Discourse (TSD), developed by Norman Fairclough, CDA has defined itself theoretically and methodologically, and this explains the relevance of the British linguist to CDA. To elaborate the TSD, Fairclough resorted to important authors of the sciences of language like Halliday, Bakhtin and Foucault, and of social sciences like Bourdieu, Giddens, Thompson, Gramsci and others. We approached the four first ones in this work, and the choice of these authors is due to our interest in the Structuralist aspects of the research of Fairclough. When we refer to structuralist bias , we raise up a great number of problematics about Structuralism, which have existed since the moment the Structuralism came to be seen with certain aversion for many language theorists. One of the reasons is the fact that structuralist approaches give priority to the social structures, not admitting the capacity of action and change of the social subject, this criticism is present in Norman Fairclough s books. Another problematic is a kind of self saturation that the proper structuralism allows to be shown. But to explain this, it is necessary to use the division that Umberto Echo (2001) makes between ontological Structuralism and methodological Structuralism. The first one consists, basically, in the incessant search of deeper structures that lead the phenomena, and the second one consists in the application of homogeneous structural models in the analysis of different phenomena. Eco criticizes the first one, showing the impossibility of reassuring, in fact, the real existence of structures, but he presents the second one as a productive methodology for many kinds of researches. In Fairclough s approach, we find the two modalities of structuralism displayed by Eco. During the research we demonstrate how important Bakhtin, Foucault, Bourdieu and Halliday, had been for the constitution of the structuralist bias of Norman Fairclough, allowing the British author to operate with systems of differences in the treatment of discursive phenomena, without neglecting the dialogic bias in the study of the interaction contexts. At last, the bakhtinian dialogism, foucaultian archaeology, the constructivist structuralist sociology of Bourdieu and the functionalist linguistic of Halliday had more been excellent supports for the constitution of the structuralist bias of Norman Fairclough s discursive approach.